2017
DOI: 10.1038/mp.2017.98
|View full text |Cite|
|
Sign up to set email alerts
|

Autism spectrum disorders and autistic traits share genetics and biology

Abstract: Autism spectrum disorders (ASDs) and autistic traits in the general population may share genetic susceptibility factors. In this study, we investigated such potential overlap based on common genetic variants. We developed and validated a self-report questionnaire of autistic traits in adults. We then conducted genome-wide association studies (GWASs) of six trait scores derived from the questionnaire through exploratory factor analysis in 1981 adults from the general population. Using the results from the Psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
122
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(130 citation statements)
references
References 57 publications
(73 reference statements)
6
122
0
2
Order By: Relevance
“…Thus, aggressive and anti-social behaviors seem to have a continuous distribution in the population, with individuals having ADHD+DBDs representing an extreme. This is in line with what has been observed for other complex phenotypes, such as diagnosed ADHD representing the upper tail of impulsive and inattention behaviors 42 , and diagnosed autism spectrum disorder representing the upper tail for social communication difficulties and rigidity 55,56 .…”
Section: Discussionsupporting
confidence: 90%
“…Thus, aggressive and anti-social behaviors seem to have a continuous distribution in the population, with individuals having ADHD+DBDs representing an extreme. This is in line with what has been observed for other complex phenotypes, such as diagnosed ADHD representing the upper tail of impulsive and inattention behaviors 42 , and diagnosed autism spectrum disorder representing the upper tail for social communication difficulties and rigidity 55,56 .…”
Section: Discussionsupporting
confidence: 90%
“…There is increasing evidence that ASD is heterogeneous, and that individual trait measures may have distinct etiologies (Happé & Ronald, ). However, for ADHD, it has been observed that the genetic correlation of ADHD as a disorder and ADHD traits approaches 1 (Demontis et al, ), and there is also genetic correlation between ASD and its associated traits (in ALSPAC [Robinson et al, ], and the Psychiatric Genetics Consortium [Bralten et al, ]). This suggests that studying ADHD/ASD traits in general populations is likely to be a powerful method that will provide useful insights into these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, common variants have been shown to be of causal significance in the disorder [14][15][16] . Although there are only few genome-wide significant SNPs identified for ASD, the cumulative polygenic variation summarized by PRS has shown to be predictive of ASD and autistic traits in the general population 17,18 . Studies have also indicated shared genetic liability of polygenic risk in ASD and psychiatric disorders 19,20 .…”
Section: Introductionmentioning
confidence: 99%